THE INFLUENCE OF KNOWLEDGE, UNDERSTANDING, AWARENESS, AND MODERNIZATION OF TAX ADMINISTRATION ON TAXPAYER COMPLIANCE INDIVIDUALS - Mutiara Chandra; Amir Indrabudiman (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the effect of knowledge, understanding, awareness, and modernization of tax administration on individual taxpayer compliance. This research uses primary data collected through questionnaires distributed to 100 individual taxpayers registered at the Jakarta Pasar Minggu Tax Office using the Simple Random Sampling method. The data were analyzed using multiple linear regression with the assistance of SmartPLS version 3.2.9 and Microsoft Excel 2021. The results indicate that knowledge, understanding, awareness, and modernization of tax administration have a positive and significant effect on taxpayer compliance. Therefore, improving these factors can enhance the level of compliance among individual taxpayers more effectively